Enhance the density of silicon carbide with the addition of nitrate-based additives - Dioktyanto, Mudzakkir; Aryanto, Didik; Noviyanto, Alfian; Yuwono, Akhmad Herman; Rochman, Nurul Taufiqu (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
Dense monolithic silicon carbide (SiC) was successfully sintered by hot-pressing at 1750 °C for 1 h under an applied pressure of 20 MPa with the addition of a nitrate-based additive. A relative density more than 99% were obtained with the addition of MgO-Y2O3 and Al2O3-Y2O3 in nitrate form, while in the oxide form they were 86.3 and 97.2%, respectively. Indeed, MgO-Y2O3 showed poor densification due to the eutectic temperature of 2110 °C, however, the addition of nitrate form of MgO-Y2O3 enhanced the densification greatly. The sintering mechanism in the nitrate-based additive is liquid phase sintering, which is identified by the presence of an oxide phase, i.e., Y2O3 in the SiC with the addition of Al2O3-Y2O3 in nitrate form. Moreover, the addition of nitrate form suppressed the grain growth of SiC, which was believed to be due to the adequate rearrangement stage during sintering.